1992
DOI: 10.1128/jb.174.24.7934-7940.1992
|View full text |Cite
|
Sign up to set email alerts
|

Molybdoenzyme biosynthesis in Escherichia coli: in vitro activation of purified nitrate reductase from a chlB mutant

Abstract: All molybdoenzyme activities are absent in chlB mutants because of their inability to synthesize molybdopterin guanine dinucleotide, which together with molybdate constitutes the molybdenum cofactor in Escherichia coli. The chlB mutants are able to synthesize molybdopterin. We have previously shown that the inactive nitrate reductase present in a chlB mutant can be activated in a process requiring protein FA and a heat-stable low-molecular-weight substance. We show here that purified nitrate reductase from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 29 publications
0
26
2
Order By: Relevance
“…However, its extent corresponds to only 5-10% of the expected level. In these reconstitution experiments, it has been suggested that the source of Mo-MPT is the purified NarGH dimer (13,15). These results contrast with those reported for DmsABC, in which no MPT or molybdenum was detected in the enzyme studied in a mobAB background (16).…”
contrasting
confidence: 56%
See 3 more Smart Citations
“…However, its extent corresponds to only 5-10% of the expected level. In these reconstitution experiments, it has been suggested that the source of Mo-MPT is the purified NarGH dimer (13,15). These results contrast with those reported for DmsABC, in which no MPT or molybdenum was detected in the enzyme studied in a mobAB background (16).…”
contrasting
confidence: 56%
“…This result contrasts with reports that the NarGH dimer purified from a mobAB mutant contains Mo-MPT (13,15). To reconcile these results, we subjected membrane-bound NarGHI holoenzyme to acid denaturation followed by I 2 and KI oxidation to produce the fluorescent Form A derivative of MPT (12).…”
Section: Effect Of the Mobab Mutation On The Presence Of Mo-mgd Inmentioning
confidence: 64%
See 2 more Smart Citations
“…In analogy to the known dinucleotide syntheses [54Ϫ56], the reaction is likely to be catalysed by a cytidylyltransferase which still remains to be demonstrated in H. pseudoflava. The reaction would also be analogous to the MobAcatalysed and MobB-catalysed formation of Mo-MGD from Mo-MPT and GTP in E. coli [57,58]. The Mo-MCD cofactor is subsequently integrated into the folding CO dehydrogenase polypeptides.…”
Section: Discussionmentioning
confidence: 99%